Narrative Review: Efektivitas Biaya Penggunaan Antibiotik untuk Penyakit Pneumonia di Rumah Sakit Indonesia - Chandra Arifin; Abd Roriq (Jurnal Ilmiah Medicamento, 2023)
Pneumonia is an acute inflammatory respiratory infection caused by microorganisms. This infection can occur from both toddlers to the elderly and if not properly then the acute respiratory inflammation process will continue to be able to cause various infectious complications. Until now, there are many choices of antibiotic therapy for their treatment, but they have not guaranteed their effectiveness both therapeutically and cost-effectively. The purpose of this study was to analyze the effectiveness and efficiency of pneumonia treatment costs in Indonesian Hospitals. The method used is a literature review approach, namely Systematic Review related to articles with cost-effectiveness analysis or Cost-effectiveness analysis of pneumonia treatment that have been published in the form of research articles. Search articles using three databases, namely Google Scholar, Pubmed, and Garudadekti. Then the selection stage or literature screening was carried out by reading the title, abstract, and continued with the full text of the research article obtained. The results obtained 14 research articles according to the inclusion and exclusion criteria regarding the cost-effectiveness of pneumonia treatment. From the research data, it can be concluded that the antibiotic cefotaxime is widely prescribed and the most cost-effective according to the ACER calculation. However, the ACER value is influenced by different drug administration for each patient, the effectiveness of treatment therapy, the costs incurred by the patient or direct medical costs.